Lesser Sac Glomangiosarcoma With Simultaneous Liver And Lymph Nodes Metastases Mimicking Small Bowel Gastrointestinal Stromal Tumor; Immunohistochemistry And Empirical Chemotherapy - Negahi, Alireza (Int Med Case Rep J, 2019)
Glomangiosarcoma is a rare malignant mesenchymal tumor. Despite malignant histopathological feature of glomangiosarcoma, metastasis was observed extremely rare in these tumors. Moreover, malignant glomus tumor with stomach origination and simultaneous metastasis to liver and lymph nodes were not reported so far. This report presented a 57-year-old male patient with an exophytic gastric glomangiosarcoma in lesser sac and simultaneous liver and lymph node metastasis.